EU counterterrorism policy a paper tiger? - Bures, Oldrich (Ashgate Pub., 2011)
This volume offers a critical analysis of the measures the European Union has taken to combat terrorism and how, in a number of key areas, EU counterterrorism policy is more of a paper tiger than an effective counterterrorism device.